The Japanese LupusPRO: A cross-cultural validation of an outcome measure for lupus. (July 2017) - Inoue, M; Shiozawa, K; Yoshihara, R; Yamane, T; Shima, Y; Hirano, T; Jolly, M; Makimoto, K
Objective: This study aimed to validate the Japanese version of the LupusPRO questionnaire for use with systemic lupus erythematosus patients. Methods: Participants were 205 lupus patients recruited from three rheumatology centers in Japan. Demographic data were collected and quality of life was assessed using the LupusPRO and the Short Form Health Survey-12. Disease activity was evaluated by physicians using the Systemic Lupus Erythematosus Activity Index. Some participants completed questionnaires 10–14 days after the first survey. Internal consistency reliability, test-retest reliability, content validity and convergent validity were examined, and confirmatory factor analysis was performed. Results: Participants' mean age was 47.8 ± 13.6 years. Older participants scored lower on physical quality of life and higher on coping than younger participants. The LupusPRO showed satisfactory test-retest reliability ( n = 111). Test-retest reliability was lower for the mental and social aspects of quality of life, indicating fluctuations in quality of life during the two-week interval. Internal consistency reliability was good and convergent validity with the corresponding domains of the Short Form Health Survey-12 was satisfactory. Confirmatory factor analysis showed a good model fit. Conclusion: The Japanese LupusPRO is a reliable and valid measure to evaluate treatment interventions for systemic lupus erythematosus.